Methodology for Selection of Spindle Drives for Milling Machines (International Journal of Engineering and Computer Science, 2017)
This paper describes a methodology for selection of spindle electric drives for milling machines with digital program control. The offered algorithm takes into account the technological process features, the tools used, the processed material, and the mechanical gear type. A concrete example has been presented, illustrating the practical application of this methodology. A number of models for computer simulation of electric drive systems with dual-zone speed regulation have been developed, allowing study at various reference speeds and loads applied to the motor shaft. The research held as well as the results obtained can be used in the development of such electric drives for the studied class of machine tools